Cladophialophora bantiana and Nocardia farcinica infection simultaneously occurring in a kidney transplant recipient: Case report and literature review. Issue 4 (15th June 2021) - Cortés, Pedro; Jane Hata, D.; Libertin, Claudia; Meza Villegas, Diana M.; Harris, Dana M.
Abstract: Solid organ transplant recipients are at increased risk of acquiring devastating infections with unusual pathogens. Nocardia are aerobic actinomycetes that affect the lungs, brain, skin and soft tissue. Cladophialophora species are dematiaceous fungi that overwhelmingly cause infections in the brain. Both organisms carry a high mortality rate. We present the first reported renal transplant case with Cladophialophora bantiana involving the renal allograft with concurrent invasive nocardiosis involving the lungs and brain. Abstract :